Workforce development and skill formation in Asia - Benson, John, 1948-; Gospel, Howard F.; Zhu, Ying, 1961- (Routledge studies in the growth economies of Asia ;, 2013)
"Asia has undergone rapid transformation over the past several decades as many countries have embraced new technologies and the processes of globalisation. Focusing on a number of developed and developing Asian economies, this book explores the dynamics of workforce development and skill formation, and considers questions of both skills shortages and skills gaps"--